Exergy Analysis in Hydrogen-Air Detonation - Abel Rouboa; Valter Silva; Nuno Couto (Journal of Applied Mathematics)
The main goal of this paper is to analyze the exergy losses during the shock and rarefaction wave of hydrogen-air mixture. First, detonation parameters (pressure, temperature, density, and species mass fraction) are calculated for three cases where the hydrogen mass fraction in air is 1.5%, 2.5%, and 5%. Then, exergy efficiency is used as objective criteria of performance evaluation. A two-dimensional computational fluid dynamic code is developed using Finite volume discretization method coupled with implicit scheme for the time discretization (Euler system equations). A seven-species and five-step global reactions mechanism is used. Implicit total variation diminishing (TVD) algorithm, based on Riemann solver, is solved. The typical diagrams of exergy balances of hydrogen detonation in air are calculated for each case. The energy balance shows a successive conversion of kinetic energy, and total enthalpy, however, does not indicate consequent losses. On the other hand, exergy losses increase with the augment of hydrogen concentration in air. It obtained an exergetic efficiency of 77.2%, 73.4% and 69.7% for the hydrogen concentrations of 1.5%, 2.5%, and 5%, respectively.